A Unique High‐Throughput Assay to Identify Novel Small Molecule Inhibitors of Chemotaxis and Migration. Issue 1 (3rd March 2017) - Liao, Xin‐Hua; Kimmel, Alan R.
Abstract: Chemotaxis and cell migration play pivotal roles in normal physiological processes such as embryogenesis, inflammation, and wound healing, as well as in pathological processes including chronic inflammatory disease and cancer metastasis. Novel chemotaxis/migration inhibitors are desirable for developing effective therapeutics and probing molecular mechanisms. We describe a fluorescence‐based phenotypic assay in a 1536‐well plate format for high‐throughput screening of novel inhibitors of chemotaxis/migration within complex libraries of thousands of compounds. Although the assay utilizes the unique cellular response properties of Dictyostelium, the compounds identified are able to inhibit chemotaxis of mammalian cells. In addition, a parallel cell cytotoxicity counter‐screen with an ATP content assay is described that eliminates cytotoxic compounds from the screen. This novel compound screening approach enables rapid identification of novel lead compounds that inhibit chemotaxis in human and other cells for drug development and research tools. © 2017 by John Wiley & Sons, Inc.